Adsorption with catalytic oxidation in a recirculating bed reactor for contaminated groundwater. (June 2018) - Russo, Analia V.; De Angelis, Laura E.; Jacobo, Silvia E.
Abstract: A novel nanoremediation concept, which is based on in situ trapping of organic contaminants by adsorption and catalytic oxidation in combination with oxidants such as hydrogen peroxide is presented. In earlier works we explored the porous structure of a modified natural clinoptilolite loaded with iron as a supported catalyst (NZ -A-Fe). The supported catalyst prevents iron release during all the process. This paper presents novel results for BTX (Benzene, Toluene and Xylene) removal from aqueous solution considering that adsorption and oxidation processes are taking place simultaneously. The experiment was achieved by fluxing an aqueous solution of BTX 3.3 mM and hydrogen peroxide, at neutral pH, using the same reservoir. After 870 min, C/C0 reaches near 10% for each pollutant. The system removed 65 mg BTX in the present conditions (13 mg/g NZ-A-Fe). The results indicate that the recirculation bed reactor is an excellent system to remove by adsorption and oxidation processes BTX from water due to high mass transfer coefficients and other advantages when compare to batch reactor experiments.